Extra-neural metastases in pediatric diffuse midline gliomas, H3 K27-altered: presentation of two cases and literature review - De Martino, Lucia; Picariello, Stefania; Russo, Carmela; Errico, Maria Elena; Spennato, Pietro; Papa, Maria Rosaria; Normanno, Nicola; Scimone, Giuseppe; Colafati, Giovanna Stefania; Cacchione, Antonella; Mastronuzzi, Angela; Massimino, Maura; et al. (Frontiers in Molecular Neuroscience, 2023)
Introduction Pediatric diffuse midline gliomas (DMG), H3 K27- altered, are the most aggressive pediatric central nervous system (CNS) malignancies. Disease outcome is dismal with a median survival of less than one year. Extra-neural metastases are an unusual occurrence in DMG and have been rarely described. Methods and results Here, we report on two pediatric patients affected by DMG with extra-neural dissemination. Their clinical, imaging, and molecular characteristics are reported here. An 11-year-old male 5 months after the diagnosis of diffuse intrinsic pontine glioma (DIPG) developed metastatic osseous lesions confirmed with computed tomography (CT) guided biopsy of the left iliac bone. The patient died one month after the evidence of metastatic progression. Another 11-year-old female was diagnosed with a cerebellar H3K27- altered DMG. After six months, she developed diffuse sclerotic osseous lesions. A CT-guided biopsy of the right iliac bone was non-diagnostic. She further developed multifocal chest and abdominal lymphadenopathy and pleural effusions. Droplet digital polymerase chain reaction (ddPCR) on pleural effusion revealed the presence of H3.3A mutation (c.83A>T, p.K28M). The patient died 24 months after the diagnosis of DMG and 3 months after the evidence of metastatic pleural effusion. Discussion Extra-neural metastasis of DMG is a rare event and no standard therapy exists. An accurate and early diagnosis is necessary in order to develop a personalized plan of treatment. Further research is needed to gain further insights into the molecular pathology of DMG, H3K27- altered and improve the quality of life and the final outcome of patients with this deadly disease.